2016
DOI: 10.3389/fnut.2016.00038
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Effects of a Single High-Fat Meal Enriched with Vegetable n-3 or a Combination of Vegetable and Marine n-3 Fatty Acids on Intestinal Peptide Release and Adipokines in Healthy Female Subjects

Abstract: Peptides released from the small intestine and colon regulate short-term food intake by suppressing appetite and inducing satiety. Intake of marine omega-3 (n-3) fatty acids (FAs) from fish and fish oils is associated with beneficial health effects, whereas the relation between intake of the vegetable n-3 fatty acid α-linolenic acid and diseases is less clear. The aim of the present study was to investigate the postprandial effects of a single high-fat meal enriched with vegetable n-3 or a combination of veget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
1
0
1
Order By: Relevance
“…In addition, fish oil, which is rich in polyunsaturated fatty acids, suppresses the postprandial GIP response more effectively than cocoa butter and olive oil [37]. However, it has been shown that in healthy young and lean females, there was no difference in postprandial GIP secretion induced by coconut fat (a source for saturated fatty acids), linseed oil, and a mixture of linseed and cod liver oil [38]. In the present study, we found that a SMART WASHOKU meal decreases serum GIP secretions during a meal tolerance test and VFA during a 2-week dietary intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, fish oil, which is rich in polyunsaturated fatty acids, suppresses the postprandial GIP response more effectively than cocoa butter and olive oil [37]. However, it has been shown that in healthy young and lean females, there was no difference in postprandial GIP secretion induced by coconut fat (a source for saturated fatty acids), linseed oil, and a mixture of linseed and cod liver oil [38]. In the present study, we found that a SMART WASHOKU meal decreases serum GIP secretions during a meal tolerance test and VFA during a 2-week dietary intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Enquanto isso, o EPA e DHA podem ser encontrados em peixes de águas profundas, como salmão, anchova, sardinha e atum. A associação entre a ingesta de ALA e doenças é menos clara do que a ingesta de EPA e DHA, visto que foi menos estudada que os ácidos graxos ômega-3 de origem marinha (NARVERUD, 2016). Considerando a realidade brasileira, onde esses peixes são provenientes de cativeiro, portanto tendo alimentação pobre em ômega-3, a melhor fonte de ômega-3 seria o ALA, inclusive com menor custo (RAJARAM, 2014).…”
Section: Discussão 5 Discussãounclassified